The enzymatic transformation of water-insoluble reactants in Nonaqueous Solvents. Conversion of cholesterol to Cholest-4-ene-3-one by a Nocardia sp. - 248859 Buckland, B. C.; Dunhill, P.; Lilli, M.D.
42